2016
DOI: 10.1590/1414-431x20165287
|View full text |Cite
|
Sign up to set email alerts
|

LXW7 ameliorates focal cerebral ischemia injury and attenuates inflammatory responses in activated microglia in rats

Abstract: Inflammation plays a pivotal role in ischemic stroke, when activated microglia release excessive pro-inflammatory mediators. The inhibition of integrin αvβ3 improves outcomes in rat focal cerebral ischemia models. However, the mechanisms by which microglia are neuroprotective remain unclear. This study evaluated whether post-ischemic treatment with another integrin αvβ3 inhibitor, the cyclic arginine-glycine-aspartic acid (RGD) peptide-cGRGDdvc (LXW7), alleviates cerebral ischemic injury. The anti-inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…An elevation in brain water content and MDA levels, along with a decline in SOD activity were observed in the NC, MCAO, and blank groups, while all the results were entirely opposite for the siRNA‐S100B group. Abundant studies have shown that patients with ischemic stroke have increased brain water content, which can result in brain edema . SOD is a brain antioxidant enzyme whose activity plays a crucial role in the diagnosis of ischemic stroke but decreases after ischemic stroke, as demonstrated by Vani et al MDA is a crucial biomarker of lipid peroxidation, which forms when the cellular membrane disrupts after leaking into blood and extracellular space, thus exacerbating IS .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…An elevation in brain water content and MDA levels, along with a decline in SOD activity were observed in the NC, MCAO, and blank groups, while all the results were entirely opposite for the siRNA‐S100B group. Abundant studies have shown that patients with ischemic stroke have increased brain water content, which can result in brain edema . SOD is a brain antioxidant enzyme whose activity plays a crucial role in the diagnosis of ischemic stroke but decreases after ischemic stroke, as demonstrated by Vani et al MDA is a crucial biomarker of lipid peroxidation, which forms when the cellular membrane disrupts after leaking into blood and extracellular space, thus exacerbating IS .…”
Section: Discussionsupporting
confidence: 92%
“…Abundant studies have shown that patients with ischemic stroke have increased brain water content, which can result in brain edema. 27,28 SOD is a brain antioxidant enzyme whose activity plays a crucial role in the diagnosis of ischemic stroke but decreases after ischemic stroke, as demonstrated by Vani et al 29 MDA is a crucial biomarker of lipid peroxidation, 30 which forms when the cellular membrane disrupts after leaking into blood and extracellular space, thus exacerbating IS. 31 Our results were also consistent with a report published by Nejad et al, suggesting that MDA level is considerably higher in patients with ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the systemic accumulation of toxins, induced by a HF diet may contribute to inflammation in the hippocampus. It has been reported that activated microglial cells release pro-inflammatory cytokines IL-1 and TNF-α, which contribute to the neurodegenerative process 46 . The activation of astrocytes is known to induce innate and adaptive immunity 47 and astroglial responses were assessed in the present study by GFAP immunostaining.…”
Section: Discussionmentioning
confidence: 99%
“…Post-ischemic inflammation, one of the main pathological features in the early stage of cerebral I/R injury, contributes to the release of pro-inflammatory mediators, which exacerbate cerebral infarction [ 39 ]. Studies have reported that TLR4 expressed on microglia and astrocytes plays a crucial role in the generation of pro-inflammatory cytokines in the initial stage of cerebral I/R injury, whereas pharmacological interventions alleviate cerebral infarction by inhibiting TLR4-mediated microglial and astrocytic activation in the ischemic area in the acute phase of transient MCAo [ 40 ].…”
Section: Discussionmentioning
confidence: 99%